Changes in Deoxyribonucleic Acid Methylation Contribute to the Pathophysiology of Multiple Sclerosis - Celarain, Naiara; Tomas-Roig, Jordi (Frontiers in Genetics, 2019)
Multiple sclerosis (MS) is an autoimmune disease of the central nervous system characterized by loss of coordination, weakness, dysfunctions in bladder capacity, bowel movement and cognitive impairment. Thus, the disease leads to a significant socioeconomic burden. In the pathophysiology of the disease, both genetic and environmental risk factors are involved. Gene x environment interaction is modulated by epigenetic mechanisms. Epigenetics refers to a sophisticated system that regulates gene expression with no changes in the DNA sequence. The most studied epigenetic mechanism is the DNA methylation. In this review, we summarize the data available from the current literature by grouping sets of differentially methylated genes in distinct biological categories: the immune system including innate and adaptive response, the DNA damage and the central nervous system.